As divisas interestaduais brasileiras: uma análise sobre a permanência do litígio territorial entre o Ceará e o Piauí - Souza, Vládia da Silva (2020)
The land disputes between the states of Ceará and Piauí date back to the colonial period, when Piauí, as captaincy of Maranhão, started to request the lands of the Mission of Ibiapaba, which were included as Ceará territory. In 1761 a Royal Order was issued that determined these lands as belonging to Ceará. In the 19th century, the territorial disagreements reignited after Ceará occupied the lands of the Amarração district in the Piauí territory. Piauí carried out several protests contesting the ownership of this locality with the imperial authorities. In an attempt to solve the standoff, D. Pedro II, promulgated decree number 3.012 on October 22, 1880, which transferred to Piauí the lands of Amarração, and granted Ceará the parish of Príncipe Imperial. Once the agreement was sealed, the territorial differences between the parties were not resolved, while today the border between Ceará and Piauí is home to a litigation of approximately 2,800 km². Considering these conflicts, this study proposes a discussion on the interstate boundaries in Brazil, with the emphasis on the existing territorial dispute between Ceará and Piauí, both located in the Northeast of Brazil. For this purpose, the objective was defined to analyze the factors that imply the permanence of the litigious issue between the states of Ceará and Piauí. In order to fullfill this aim, it was settled as a main objective: to discuss how the republican constitutions dealt with interstate boundaries issues; to understand the genesis of the conditioning factors that led to the indefinition of the boundaries between the states of Ceará and Piauí; to understand how deliberative institutions and research institutes dedicated to territorial studies have discussed for the unfolding of this litigation; to identify the social, economic and infrastructure aspects of the municipalities involved in the litigation. The methodology used consisted of a case study that allowed a literature review on the proposed theme; analyze the republican constitutions, interview the deliberative institutions and research institutes involved in the litigation, analyze the speeches contained in journalistic articles, observe the position of the representations from Ceará and Piauí before the public hearings held to discuss this litigious divergence, study the economic potentialities of Serra da Ibiapaba and consult the social, economic and infrastructure indicators of the municipalities involved in the litigation. The methodology adopted in this study allowed us to understand that the land conflict between Ceará and Piauí is currently based on economic, political and fiscal issues. In terms of economy, entra“Serra da Ibiapaba” is evident with the potential for farming, tourism and the entry of capital injection to invest in wind power. In political terms, it aims to expand and/or maintain political power, since the population represents an increase in the number of votes, increasing the possibilities of bringing local and state political leaders to power. In fiscal terms, we note the dispute for financial resources from the federal government and the increase in the tax collection capacity of municipalities, both influenced by the size of the population. The joint action of economic, political and fiscal factors exacerbates disputes over land in Ibiapaba and implies the permanence of the land dispute between Ceará and Piauí.